Predicting Community Engagement? The Carnegie Foundation's Elective Classification - Andrew J. Pearl (The University of Alabama, 2022)
The Carnegie Foundation's elective Community Engagement classification is valuable for colleges and universities seeking to demonstrate a mutually beneficial relationship with the community. This study uses logistic regression analysis to identify predictive institutional characteristics for applying for and receiving the Community Engagement classification. The findings suggest that publicly available institutional financial variables are not predictive of an institution applying for and receiving the classification.